Cultivation of Aschersonia placenta Berkeley and Broom and its efficacy for controlling Parlatoria ziziphi (Lucas) (Hemiptera: Diaspididae) - Homrahud, Dokgluaymai; Uraichuen, Sopon; Attathom, Tipvadee (Agriculture and Natural Resources, 2016)
The entomopathogenic fungus genus Aschersonia (Deuteromycotina: Hyphomycetes) is host specific to some aleyrodids and scale insects. In search of the Thai endemic species, fungus samples were isolated from cadavers of citrus whiteflies (Aleyrodes tabaci Gennadius) found in citrus orchards in Trat province, Thailand. After morphological analysis and scanning electron microscopic examination, it was identified as Aschersonia placenta Berkeley and Broom. Seven synthetic media, namely: potato dextrose agar (PDA), PDA with pasteurized milk (Foremost®) (PDA + M), Sabouraud dextrose agar with yeast extract (SDAY), SDA with pasteurized milk (Foremost®) (SDA + M), corn meal agar (CMA), water agar with juice of eight vegetable species (V8®) (WA + V8) and WA were explored as appropriate media for fungal cultivation. SDAY and SDA + M gave the best colony radial growth, producing 2.04 ± 0.13 cm and 2.09 ± 0.10 cm in 21 d, respectively. However, based on the ability of A. placenta to produce conidia, PDA and SDAY which produced 2.59 x 108 conidia/mL and 2.69 x 108 conidia/mL, respectively, were considered as the most suitable media for this fungal species. The efficiency assessment of A. placenta for controlling black parlatoria (Parlatoria ziziphi (Lucas)), indicated that a conidial suspension at 1 x 109 conidia/mL gave 23.73% and 27.42% mortality at 14 and 21 d post inoculation, respectively.